How to ruin the holidays [videorecording (DVD)] - Nash, Amber; Mochrie, Colin, 1957-; Davis, Luke; Lambert, Kate; Tyler, Aisha; Zebrowski, Henry; Chieng, Ronny; Aaron, Caroline; Gillese, Kevin (Buffalo 8, 2023)
A struggling comedian is lured home for the holidays, and she works to redefine her relationships with her father and siblings. When her dad's unconventional lifestyle comes to light, she must face a life-chaning decision about caring for her brother with disabilities.